2020
DOI: 10.32598/bcn.11.6.1775.1
|View full text |Cite
|
Sign up to set email alerts
|

Dalteparin as a Novel Therapeutic Agent to Prevent Diabetic Encephalopathy by Targeting Oxidative Stress and Inflammation

Abstract: Introduction: Hepcidin is the main modulator of systemic iron metabolism, and its role in the brain has been clarified recently. Studies have shown that hepcidin plays an important role in neuronal iron load and inflammation. This issue is of significance because neuronal iron load and inflammation are pathophysiological processes that are highly linked to neurodegeneration. Moreover, the activity of hepcidin has recently been manipulated to recover the neuronal impairment caused by brain inflammation in anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Interestingly, the level of ferritin was significantly increased in the hippocampus of T1DM rats, without distinguishing between FTL and TFH. 62 This seems to indicate differential regulation of ferritin in different types of DM brains, which requires further investigation of the specific mechanisms.…”
Section: Mechanisms Of Brain Iron Deposition In DCImentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the level of ferritin was significantly increased in the hippocampus of T1DM rats, without distinguishing between FTL and TFH. 62 This seems to indicate differential regulation of ferritin in different types of DM brains, which requires further investigation of the specific mechanisms.…”
Section: Mechanisms Of Brain Iron Deposition In DCImentioning
confidence: 99%
“… 72 , 73 This may be due to the characteristics of different diabetic patients and the complex regulatory factors of hepcidin, but may the same be true of hepcidin levels in the brain? 62 More experimental and clinical studies are needed to confirm or refute the specific role of hepcidin in DM.…”
Section: Factors Of Diabetic Brain Iron Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, enoxaparin was found to prevent the formation of ApoE4-Aβ complexes by binding to them [170]. In another study, dalteparin, a low molecular weight heparin, was found to reduce oxidative stress and inhibit the inflammatory response in the hippocampus of the streptozotocin-induced model, leading to an improvement in cognitive impairment [171]. Heparin is an anticoagulant that is primarily administered as an intravenous or subcutaneous injection to treat thrombotic disorders such as acute myocardial infarction and pulmonary embolism [163][164][165][166][167][168][169][170].…”
Section: Novel Therapeutic Approach To the Control Of Blood-borne Pro...mentioning
confidence: 99%
“…In addition, enoxaparin was found to prevent the formation of ApoE4-Aβ complexes by binding to them [170]. In another study, dalteparin, a low molecular weight heparin, was found to reduce oxidative stress and inhibit the inflammatory response in the hippocampus of the streptozotocin-induced model, leading to an improvement in cognitive impairment [171].…”
Section: Novel Therapeutic Approach To the Control Of Blood-borne Pro...mentioning
confidence: 99%